2013
DOI: 10.1093/scan/nst162
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to facial expressions support the role of the amygdala in processing threat

Abstract: The amygdala is known to play an important role in the response to facial expressions that convey fear. However, it remains unclear whether the amygdala's response to fear reflects its role in the interpretation of danger and threat, or whether it is to some extent activated by all facial expressions of emotion. Previous attempts to address this issue using neuroimaging have been confounded by differences in the use of control stimuli across studies. Here, we address this issue using a block design functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 33 publications
5
69
1
Order By: Relevance
“…A similar limbic-motor interaction has been shown in CD patients presenting with movement disorders during an implicit emotion task (processing of emotional-fearful and happy-faces) with increased amygdala and SMA functional connectivity along with some evidence of a failure to habituate to emotional stimuli [5]. This is important since it is well established that the amygdala is a key limbic system structure in emotion recognition and in particular identification of threat signals [6,7]. Its connection to motor loops is essential in order to interrupt ongoing motor activities in potentially threatening situations [8].…”
Section: Introductionsupporting
confidence: 57%
“…A similar limbic-motor interaction has been shown in CD patients presenting with movement disorders during an implicit emotion task (processing of emotional-fearful and happy-faces) with increased amygdala and SMA functional connectivity along with some evidence of a failure to habituate to emotional stimuli [5]. This is important since it is well established that the amygdala is a key limbic system structure in emotion recognition and in particular identification of threat signals [6,7]. Its connection to motor loops is essential in order to interrupt ongoing motor activities in potentially threatening situations [8].…”
Section: Introductionsupporting
confidence: 57%
“…Mattavelli et al, 2013). Instead, we were able to track the magnitude of perceived differences between emotions, and to demonstrate that this pattern of between-category differences could still be modelled both from normalized image properties and from neural responses in STS.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to these findings, N’Diaye et al (2009) and Sarkheil et al (2013) did not observe any significant intensity effects in amygdalar activation for fearful, angry, and happy facial expressions when dynamic facial expressions were used. Another block design study by Mattavelli et al (2014) used fearful, angry, disgusted, sad, neutral and happy expressions and manipulated happy expressions in two intensities (100 and 25%), showing that threat-related expressions (e.g., fearful and angry) produced stronger activity in the amygdala than did neutral and 25% happy expressions, but no other effects were significant. Because not all negative expressions enhanced amygdalar activation than did neutral expressions and there was no intensity effect for happy expressions, the authors suggested that the amygdalar activation is associated with threat, but not valence or arousal, at least during face processing.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the analytical strategy was not apt to detect the presence of valence-independent intensity effects. For experimental design, Morris et al (1996) and Mattavelli et al (2014) adopted a block design, which is known to be prone to cause habituation, expectation, and regulation effects. These unwanted effects might have decreased the impact of intensity (see Breiter et al, 1996; Wright et al, 2001).…”
Section: Introductionmentioning
confidence: 99%